PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEBSITE PREZI KELAS V SEKOLAH DASAR PADA MATERI HURUF KAPITAL - Nafisah, Nida; Kurniaman, Otang; Astuti Mulyani, Eva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low understanding of fifth grade elementary school students regarding the use of capital letters and the lack of interactive learning media used in Indonesian language learning. This study aimed to develop an interactive learning media using the Prezi website on capital letter material for fifth grade elementary school students that is valid and practical. This research used the Research and Development (R&D) method with the 4D development model consisting of define, design, develop, and disseminate stages. The subjects of this study were fifth grade students and teachers at elementary school. Data collection techniques used validation sheets and practicality questionnaires. The results showed that the interactive learning media developed obtained a validity percentage from media experts of 91.6% with a very valid category, material experts of 98% with a very valid category, and language experts of 92.5% with a very valid category. The practicality test results obtained a percentage of 90.6% from students and 89% from teachers with a very practical category. Therefore, the interactive learning media using the Prezi website on capital letter material is feasible and practical to be used in the learning process for fifth grade elementary school students.